Utang Luar Negeri, Penanaman Modal Asing dan Kesejahteraan Masyarakat: Studi pada Tujuh Negara ASEAN - Ngatini, Ngatini (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
External debt and foreign direct investment (FDI) in seven countries in the Southeast Asian Region have increased by more than 40% over the period 2014-2021. Likewise, gross domestic product (GDP) per capita over eight years has grown by 25%. When compared to countries in the European Region, external debt and FDI grew by only 7% and 17%. Meanwhile, in African countries, external debt increased at a very high rate of almost 70%. Given the high increase in external debt and FDI in seven ASEAN countries, this study analyzed whether external debt and foreign direct investment (FDI) are a driving factor for increasing gross domestic product (GDP) per capita in seven ASEAN Countries, by including a set of control variables such as inflation and human development index (HDI). The research uses quantitative methods with the panel data for eight years from 2014 to 2021 obtained from several resources, namely International Debt Statistics, World Bank, UNCTAD Statistics and The Global Economy. The multiple linear regression fixed effect model with robust estimator of the feasible general least square (FGLS) with panel-corrected standard errors (PCSE) was used to overcome heteroscedasticity and autocorrelation. The results of the analysis found that external debt and HDI have a significant and positive effect on the GDP per capita. In contrast, inflation and FDI actually affect GDP per capita adversely. It shows that external debt is still needed as a policy instrument to finance development projects that are productive for increasing public welfare. This study recommends attracting greater foreign direct investment and allocating it to productive economic sectors.